Efficacy of topical mineralocorticoids in a rabbit model of ocular inflammation - Kıvılcım, Muhamet (The European Research Journal, 2023)
Objectives: The aim of this study was to determine the efficacy of mineralocorticoids in the treatment of ocular inflammation, whose potential use has not been assessed. Methods: Thirty-five New Zealand albino rabbits were used in the study. Rabbits were divided into five groups. Only one eye was used for experimental purposes and the other eye was used as control. 11-deoxycortisol, deoxycorticosterone acetate, fludrocortisone acetate, aldosterone and 11-deoxycorticosterone were studied in a rabbit model of ocular inflammation. All animals in a group received the same corticosteroid. Paired t-tests and analysis of variance between subjects (ANOVA) were used to evaluate efficacy. Results: The eyes treated with 11-deoxycortisol, deoxycorticosterone acetate, and fludrocortisone acetate had statistically significant lower fluorescence compared to control eyes. 11-deoxycortisol and deoxycorticosterone acetate provided a greater reduction in fluorescence compared to other corticosteroids. Conclusions: Topical use of corticosteroids, especially those with mineralocorticoid activity can decrease ocular inflammation in a rabbit model. Clinical application of topical mineralocorticoids in human ocular inflammation needs to be performed.